The ATM signaling network in development and disease - Stracker, Travis H.; Roig, Ignasi; Knobel, Philip A.; Marjanovic, Marko (Frontiers in Genetics, 2013)
The DNA damage response (DDR) rapidly recognizes DNA lesions and initiates the appropriate cellular programs to maintain genome integrity. This includes the coordination of cell cycle checkpoints, transcription, translation, DNA repair, metabolism and cell fate decisions, such as apoptosis or senescence(Jackson and Bartek, 2009). DNA double-strand breaks (DSBs) represent one of the most cytotoxic DNA lesions and defects in their metabolism underlie many human hereditary diseases characterized by genomic instability(Stracker and Petrini, 2011;McKinnon, 2012). Patients with hereditary defects in the DDR display defects in development, particularly affecting the central nervous system (CNS), the immune system and the germline, as well as aberrant metabolic regulation and cancer predisposition. Central to the DDR to DSBs is the ATM kinase, a master controller of signal transduction. Understanding how ATM signaling regulates various aspects of the DDR and its roles in vivo is critical for our understanding of human disease, its diagnosis and its treatment. This review will describe the general roles of ATM signaling and highlight some recent advances that have shed light on the diverse roles of ATM and related proteins in human disease.